Twitter sentiment as a weak signal in venture capital financing - Tumasjan, Andranik; Braun, Reiner; Stolz, Barbara (Journal of Business Venturing, 2021)
How do venture capitalists (VCs) incorporate weak and strong signals in the valuation of technology-based startups? Based on a sociocognitive perspective of signaling theory, we introduce Twitter sentiment as a novel and weak signal, which we juxtapose with patents as a traditional, strong signal. While we find a positive association between both signals and VCs' venture valuations, our results reveal that Twitter sentiment does not correlate with actual long-term investment success, whereas patents do. Additionally, we identify and test novelty and experience characteristics (i.e., startup age and VC firm experience) as boundary conditions for our proposed signal-valuation relationships.